IMPLEMENTASI BIMBINGAN DAN KONSELING UNTUK MENGATASI PERUNDUNGAN DI TINGKAT BAWAH DI PONDOK PESANTREN - Agus Qowiyuddin; Miftachul A'yun Nisa; Moch Kholili (Program Studi Pendidikan Soiologi Antropologi, FKIP-UNS, 2023)
This research is related to the phenomenon of bullying in Islamic boarding schools and focuses on the effectiveness of guidance and counseling. Using qualitative descriptive methods, This study aims to learn more deeply related to the phenomenon of bullying as well as solutions to overcome bullying violence. the study identified three main themes: